0075 Nitrergic Neurons of the Dorsal Raphe Nucleus Encode Information About Stress Duration. (27th April 2018) - Nichols-Obande, I S; Anderson, S; Bush, B; Gray, C; Ehlen, J C; Jones, M I; Ananaba, G; Okere, C O; Brager, A; Paul, K
Abstract: Introduction: Nitrergic neurons of the dorsal raphe nucleus (DRN) are involved in the regulation of stress and sleep. Stress duration is an important variable to consider when discussing the response to stress because duration has been shown to have different effects on behavioral processes such as sleep. Duration of acute stress also affects intensity of HPA axis activation. Until now, the effects of acute stress duration on nitric oxide synthase activity have not been revealed. Methods: Here NADPH-d was used as an index of NOS activity in rats that were restrained for either 1, 3, or 6 hours. Results: These experiments revealed increased NOS activity through 6 hours of restraint in the caudal lateral wings and ventromedial sub-regions. Conclusion: These data suggest that, NOS neurons may play a dynamic role in the response to stress duration. Future studies will determine the role of stress duration on sleep-wake states. Support (If Any): This work was supported in part from the NIH: MBRS-RISE grant #5R25GM060414 and NIH-R01 NS078410.